SOCIALIZATION AND MAKING OF LEARNING VIDEOS WITH BANDICAM AND FILMORA APPLICATIONS FOR LECTURERS OF STIKES DHARMA LANDBOUW PADANG - Maisa Putra, Deni; Zhuhriano Yasli, Dicho; Srimayarti, Berly Nisa; Leonard, Devid (LPPM Univ. Ibn Khaldun Bogor, 2022)
During the Covid-19 pandemic, Lecturers were able to improve their ability to make learning media because the lecture process was carried out boldly. To provide debriefing to lecturers who need training for making learning media with software. Understanding of information, in this case, making learning videos with bandicam and filmora applications. Mastery and understanding of practical programming languages, which can be applied directly, the results can be seen, are soft skills that must be taught by lecturers to teach courses during the Covid-19 pandemic. At the moment. This activity was attended by STIKES Dharma Landbouw Padang Lecturers, on Saturday, January 9, 2021, by explained the material and practice of making learning media.